High-grade carotid artery stenosis: A forgotten area in cardiovascular risk management. (September 2016) - Good, Elin; Länne, Toste; Wilhelm, Elisabeth; Perk, Joep; Jaarsma, Tiny; de Muinck, Ebo
Background: Patients with high-grade (≥70%) carotid artery stenosis (CAS) rank in the highest risk category for future cardiovascular (CV) events, but the quality of cardiovascular risk management in this patient group is unknown. Design: Cross-sectional retrospective study. Methods: Data were collected for all patients diagnosed with high-grade CAS in Östergötland county, Sweden between 1 January 2009 and 31 July 2012 regarding the quality of cardiovascular risk management, co-morbidity and outcomes during the 2-year follow-up period after a diagnosis of CAS with a carotid ultrasound scan. Patients were included regardless of whether they underwent carotid endarterectomy (CEA). Results: A total of 393 patients with CAS were included in the study; 133 (33.8%) underwent CEA and 260 (66.2%) were assigned to a conservative management (CM) group. In both groups of patients the prescription of platelet inhibitors, statins and antihypertensive drugs increased significantly ( p  < 0.001) after diagnosis. However treatment targets were not met in the majority of patients and the low-density lipoprotein level was on target in only 13.5% of patients. During follow-up, low-density lipoprotein levels were not measured in 19.8% of patients who underwent CEA and 44.2% of patients in the CM group ( p  < 0.001); HbA1c was not measured in 24.4% of patients with diabetes in the CEA group and in 18.8% of patients in the CM group ( p  = 0.560). There was no documentation of counselling on diet, exercise, smoking cessation or adherence to medication. The combined clinical event rate (all-cause mortality, cardiovascular mortality and non-fatal cardiovascular events) was high in both groups (CEA 36.8% and CM 36.9%; p  = 1.00) with no difference in the occurrence of ipsilateral ischaemic stroke. Conclusions: The clinical event rate was high in patients with high-grade CAS and the management of cardiovascular risk was deficient in all aspects.